Secularphobia di Indonesia: Ruqyah Intelektual sebagai Terapinya - Hidayati, Laily (Proceedings of Annual Conference for Muslim Scholars, 2019)
Abstract: Differences in views about secularism and secularization in details, not principles, among Indonesian Muslim intellectuals is a complete academic discourse that will enrich insights and give some great intellectual contribution related to the relations or state and religion, which in the course of Indonesian nationalism continues to improve the process increasingly complex developments. In the case of Indonesia, discussing the relationship between religion and state is a crucial debate. However, the role of religion in relations with the state always determines an important position, if not decisive. Religious domination goes beyond this to the realm of the total constitution, except as a source of inspiration. Although the view is very clear, that secularism is one thing that we can’t deny as a logic consequence of modernity, now we wonder and wonder, asking who can easily label evil, depraved, cruel, or immoral, to people who are not religious (or do not show the symbol of their religion). Why do community groups or parties so seriously decide about education participation in Indonesia? Why is a group of people or several parties strongly opposed and doubtful about the election of religious ministers who are not of religious leaders? In fact what happens is that, in the realm of unconsciousness with these groups, they are buried in critical thoughts and feelings of inferiority because they fail to understand the teachings of their own religion. This failure is caused by immature people who respond to the flow of modernity - then the flow of secularization.